Early Effect of the Circular Model of Kidney Allocation in the United States. Issue 1 (27th January 2023) - Puttarajappa, Chethan M.; Hariharan, Sundaram; Zhang, Xingyu; Tevar, Amit; Mehta, Rajil; Gunabushanam, Vikraman; Sood, Puneet; Hoffman, William; Mohan, Sumit
Abstract : Significance Statement: To reduce geographic disparities in kidney transplantation, the United States implemented a new model of deceased donor kidney allocation in March 2021. The new model's effect on transplant logistics and kidney utilization is unknown. Using data from the Scientific Registry of Transplant Recipients, this study found an increase in transplants among highly sensitized patients and patients with long dialysis duration. However, cold ischemia time after implementation of the new allocation policy increased significantly, with a suggestion of an increase in kidney discards. Given that the policy was implemented during the coronavirus disease 2019 pandemic, which also affected transplant practices, there is need for continued monitoring for potential unintended consequences of the new policy, along with efforts to mitigate them. Abstract : Background: In March 2021, the United States implemented a new kidney allocation system (KAS250) for deceased donor kidney transplantation (DDKT), which eliminated the donation service area-based allocation and replaced it with a system on the basis of distance from donor hospital to transplant center within/outside a radius of 250 nautical miles. The effect of this policy on kidney discards and logistics is unknown. Methods: We examined discards, donor-recipient characteristics, cold ischemia time (CIT), and delayed graft function (DGF) during the first 9 months of KAS250 compared with a pre-KAS250 cohort from the preceding 2 years. Changes in discards and CIT after the onset of COVID-19 and the implementation of KAS250 were evaluated using an interrupted time-series model. Changes in allocation practices (biopsy, machine perfusion, and virtual cross-match) were also evaluated. Results: Post-KAS250 saw a two-fold increase in kidneys imported from nonlocal organ procurement organizations (OPO) and a higher proportion of recipients with calculated panel reactive antibody (cPRA) 81%–98% (12% versus 8%; P <0.001) and those with >5 years of pretransplant dialysis (35% versus 33%; P <0.001). CIT increased (mean 2 hours), including among local OPO kidneys. DGF was similar on adjusted analysis. Discards after KAS250 did not immediately change, but we observed a statistically significant increase over time that was independent of donor quality. Machine perfusion use decreased, whereas reliance on virtual cross-match increased, which was associated with shorter CIT. Conclusions: Early trends after KAS250 show an increase in transplant access to patients with cPRA>80% and those with longer dialysis duration, but this was accompanied by an increase in CIT and a suggestion of worsening kidney discards.